Pengaruh Pemilihan Pelarut dalam Ekstraksi Klorofil pada Rumput Laut Gracilaria sp. dan Caulerpa sp. Segar dan Kering - Maria Malida Vernandes Sasadara; Ni Made Dwi Mara Widyani Nayaka; Putu Era Sandhi Kusuma Yuda; Erna Cahyaningsih; Ni Luh Kade Arman Anita Dewi (Jurnal Ilmiah Medicamento, 2023)
Seaweed is a photosynthetic organism, thus a good source of pigment-producing. Pharmaceutical, food, and cosmetic industries widely use chlorophyll pigments for their products. Bulung Sangu (Gracilaria sp.) and Bulung Boni (Caulerpa sp.) are widely grown seaweeds in the waters of Bali. Pre-extraction steps such as drying and solvent selection can affect pigment extraction. This study aimed to evaluate the effect of solvent selection in the extraction of chlorophyll in fresh and dried Bulung Sangu (Gracilaria sp.) and Bulung Boni (Caulerpa sp.). The solvents used were ethanol, methanol, and acetone. Estimation of chlorophyll content was carried out using UV-VIS spectrophotometry. Data were analyzed statistically using one-way ANOVA with a 95% confidence level. The results showed that the extraction of Bulung Sangu (Gracilaria sp.) on dry samples using acetone produced a total chlorophyll of 574.1 ± 33.2 g/g. Bulung Boni (Caulerpa sp.) extraction of fresh samples using methanol resulted in the highest total chlorophyll (10235.3 ± 50.3 g/g). In conclusion, drying and solvent selection affect the extraction of chlorophyll from Bulung Sangu (Gracilaria sp.) and Bulung Boni (Caulerpa sp.).